ISLAM, KEINDONESIAAN, DAN KEMANUSIAAN (TELAAH PEMIKIRAN AHMAD SYAFII MAARIF) - Damanhuri Damanhuri (Pascasarjana UIN ANTASARI Banjarmasin, 2015)
This paper explores the ideas of Islam, Indonesian-ness and humanity in thecontext of a neo-modernist thinker of Islam Indonesia, Ahmad Syafii. Histhoughts on Islam are the results of his understandings of the role of ethicsof the Koran in shaping attitudes and behavior of Muslims. Therefore, theimpressions of peaceful and dynamic value become values that should begrounded in humanity and Indonesian-ness.